2005
DOI: 10.1213/01.ane.0000150961.24747.98
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tramadol and Its Metabolite on Glycine, ??-Aminobutyric AcidA, and N-Methyl-d-Aspartate Receptors Expressed in Xenopus Oocytes

Abstract: We assessed the effects of tramadol, a centrally acting analgesic, and its major metabolite, on neurotransmitter-gated ion channels. Tramadol binds to mu-opioid receptors with low affinity and inhibits reuptake of monoamines in the central nervous system. These actions are believed to primarily contribute to its antinociceptive effects. However, little is known about other sites of tramadol's action. We tested the effects of tramadol and its M1 metabolite (0.1-100 microM) on human recombinant neurotransmitter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 21 publications
1
59
0
1
Order By: Relevance
“…However, it has been described that tramadol produces analgesic activity by modulation of monoamines like noradrenaline and serotonin, but also by GABAergic neurotransmission. 33 Moreover, it is considered that mechanisms of action of tramadol involve a partial action through µ-opioid receptors, 34 which is in accord with our results because the presence of naloxone partially reverted the antinociceptive effect of this analgesic drug in all models experienced in our study.…”
supporting
confidence: 89%
“…However, it has been described that tramadol produces analgesic activity by modulation of monoamines like noradrenaline and serotonin, but also by GABAergic neurotransmission. 33 Moreover, it is considered that mechanisms of action of tramadol involve a partial action through µ-opioid receptors, 34 which is in accord with our results because the presence of naloxone partially reverted the antinociceptive effect of this analgesic drug in all models experienced in our study.…”
supporting
confidence: 89%
“…The exact mechanism of tramadol in induction of seizure remains to be elucidated yet. Research indicates that in high concentrations tramadol exerts an inhibitory effect on gammaaminobutyric acid (GABA) receptors [12,13]. Inhibition of GABA receptors has been found to potentiate the severity of seizures in animal models [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Although the mechanism by which tramadol delays ejaculation has not been elucidated, numerous laboratory studies have shown that tramadol acts as a mild m-opioid agonist, 23 N-methyl-D-aspartate receptor antagonist. 53 5-hydroxytryptamine type 2C receptor antagonist, 54 5-nicotinic acetylcholine receptor antagonist, 55 M1 and M3 muscarinic acetylcholine receptor antagonist, 56 and a serotonin and norepinephrine modulator. 23 It is possible that one or a combination of these effects leads to a delay in ejaculation.…”
Section: Discussionmentioning
confidence: 99%